MOTIVATION FACTORS AND ITS IMPACT ON THE JOB PERFORMANCE - Rawan I. Khezendar; Yosra Hamas (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Motivation is a combination of desires and energy of an individual that are directed for achieving the different goals. For increasing the productivity of the employees, motivation plays an effective role. This paper aims to examine different motivation factors and its impact on the job performance. In this paper, five factors have been discussed. These include job satisfaction, respect, benefits, communication, and team work. For achieving the aims of the study, data was gathered by using quantitative approach. Questionnaire has been used as a primary data collection tool to gather data and the questionnaire is distributed to 40 respondents. Results of the study showed that there is a direct relation between the motivational factors and the employee job performance. It has been analysed that job satisfaction helped the employees to perform better. The incentives and benefits for the high performance, effective employee- manager communication and the good team work played a major and significant role in motivating the employees.